San Miguel : expanding the amaranth market - Elias, Jaan (SAGE knowledge. Cases., 2016)
Benito Manrique, his brother Diego, and Bruno Pagliai founded a small amaranth factory in the out-of-the-way Mexican village of Huixcazdha. Despite the plant's unschooled work force, the company had pioneered the processing of amaranth into a number of unique products. The company also had played a significant role in the development of the small community in which it was located. The company's primary customer had been the governments of Mexican states that used San Miguel's products in their dietary programs. Amaranth has many nutritional properties. It is gluten free and high in protein, containing essential amino acids not present in other vegetative food sources. In spite of these qualities, the amaranth market had never really taken off. This case study discusses this topic.